Cardiovascular evaluation for physical activity and sports - Iglesias, Diego Esteban (Revista del Hospital Italiano de Buenos Aires, 2013)
Physical activity and regular participation in sports generates recognized health benefits. However there is a small risk associated with this practice. Major cardiovascular events that may occur during or immediately after exercise include Sudden Death and Acute Myocardial Infarction. These events are mostly preventable if a pre-competitive or pre-participation medical screening is done focusing on the detection of those congenital or acquired cardiovascular diseases that can potentially cause these events